Assessing the Value of Incomplete University Degrees: Experimental Evidence from HR Recruiters - Andrea Diem; Christian Gschwendt; Stefan C. Wolter (CESifo GmbH, 2025)
A university degree is a risky investment because of the non-negligible risk of having to drop out of university without graduating. However, the costs of this risk are controversial, as it is often argued that even an uncertified year of study has a value in the labor market. To determine this value causally, however, alternatives to studying must also be considered, which is done here with the help of a discrete choice experiment with a representative sample of over 2,500 HR recruiters. The result is that dropping out of university with a major closely related to an advertised job leads to similar labor market outcomes as if someone had not studied at all. Without a direct link to a job, however, dropping out of university significantly reduces lifetime earnings. Furthermore, HR recruiters clearly prefer applicants who have used the years without studying for human capital accumulation in an alternative way, for example in the form of a traineeship.
Keywords: I26; J23; J24; J31; M51; 330; dropouts; hiring decisions; discrete choice experiment; sheepskin effect; willingness to pay; tertiary education